Influence of anthropometric factors and physical activity on blood pressure in adolescents from Taguatinga, Federal District, Brazil - Sebastião Lobo Silva; Bibiano Madrid; Clarice Maria Martins; José Luiz Queiroz; Maurilio Tiradentes Dutra; Francisco Martins Silva (Desafio Singular, 2013)
This study aimed to analyze the influence of body mass index (BMI) and physical activity level (PAL) on blood pressure (BP) in adolescents. The sample was composed of 799 students of both genders, aged 12.09 (± 0.80). The weight, height and BP were assessed according to internationally established criteria, and BMI was calculated and classified according to the cutoff points proposed by Cole, Flegal and Dietz (2000). To evaluate the PAL, the modified lifestyle questionnaire was used (Silva, Silva, & Martins, 2006). We found that 9.1% of the subjects evaluated have high blood pressure, 11.8% were overweight, 5.4% were obese and 47.2% of the people presented low PAL. The fact of being inactive (OR = 1.99), insufficiently active (OR = 1.87) and obese (OR = 5.1) was associated with an increased risk of developing hypertension. Being inactive or insufficiently active was strongly associated with the development of the obesity (OR = 7.97 and 4.35) respectively. In the studied sample, the overweight, the obesity and low PAL are associated with the development of arterial hypertension. In addition, a low PAL is associated with an increasing number of overweight adolescents.